The analysis of factors influencing patient choice of healthcare providers between tertiary hospitals and community clinics - Wu, Silin; Lei, Zhaoxia; Liu, Tinglian; Chen, Lan; Qin, Yang (Frontiers in Public Health, 2025)
BackgroundThe uneven distribution of medical resources in China has led to persistently low utilization rates of primary healthcare institutions. The tiered healthcare delivery system aims to optimize resource allocation and strengthen primary care, yet patient preferences for tertiary hospitals hinder its effective implementation. Understanding the factors influencing healthcare-seeking behaviors is crucial for improving policies and promoting system efficiency.ObjectiveTo analyse the factors influencing patient choices between a tertiary hospital and a community health service center in Chengdu and provide recommendations for advancing the tiered healthcare system.MethodsA random sampling method was used in August 2023 to survey patients at a tertiary hospital (Group A) and a community health service center (Group B). The survey assessed demographics, health status, factors influencing provider choice, and awareness of the family doctor system. Chi-square, t-tests, or Wilcoxon rank-sum tests were used for group comparisons, while logistic regression identified factors associated with primary care visits.ResultsAmong 865 valid responses (Group A: 420; Group B: 445; 92.02% response rate), Group A had significantly higher education levels and household incomes (p < 0.001), while Group B had higher chronic disease prevalence and family doctor contract rates (71.5% vs. 59.3, 44.5% vs. 25.5%; both p < 0.01). Positive factors for choosing community healthcare included better equipment and medication availability (46.9%), lower costs with higher reimbursement (45.0%), and convenient transport (41.2%). Negative factors included distrust in community care quality (39.1%) and limited familiarity with family doctors (32.8%). Logistic regression indicated that being over 60 years old (OR: 1.94, CI: 1.02–3.69) and awareness of the tiered healthcare system (OR: 2.48, CI: 1.56–3.96) were significant factors for seeking primary care.ConclusionPatients with higher education and income prefer tertiary hospitals, while chronic disease patients are more likely to utilize community care. Low family doctor contract rates and trust in community healthcare quality remain barriers. Strengthening community resources and promoting the tiered healthcare system could improve patient participation and alleviate pressure on tertiary hospitals.